In-situ glyoxalization during biosynthesis of bacterial cellulose. (1st August 2015) - Castro, Cristina; Cordeiro, Nereida; Faria, Marisa; Zuluaga, Robin; Putaux, Jean-Luc; Filpponen, Ilari; Velez, Lina; Rojas, Orlando J.; Gañán, Piedad
Highlights: We developed a novel method to synthesize highly crosslinked bacterial cellulose (BC). Strong crosslinked networks were formed between extruded cellulose ribbons by reaction with the glyoxal precursors. The crystalline structure of cellulose was preserved while the acidic component of the surface energy was reduced. The glyoxalization is expected to facilitate other modifications upon biosynthesis of cellulose ribbons by microorganisms. Abstract: A novel method to synthesize highly crosslinked bacterial cellulose (BC) is reported. The glyoxalization is started in-situ, in the culture medium during biosynthesis of cellulose by Gluconacetobacter medellensis bacteria. Strong crosslinked networks were formed in the contact areas between extruded cellulose ribbons by reaction with the glyoxal precursors. The crystalline structure of cellulose was preserved while the acidic component of the surface energy was reduced. As a consequence, its predominant acidic character and the relative contribution of the dispersive component increased, endowing the BC network with a higher hydrophobicity. This route for in-situ crosslinking is expected to facilitate other modifications upon biosynthesis of cellulose ribbons by microorganisms and to engineer the strength and surface energy of their networks.